login
A001099
a(n) = n^n - a(n-1), with a(1) = 1.
4
1, 3, 24, 232, 2893, 43763, 779780, 15997436, 371423053, 9628576947, 275683093664, 8640417354592, 294234689237661, 10817772136320355, 427076118244539020, 18019667955465012596, 809220593930871751581, 38537187481365665823843, 1939882468178947923300136
OFFSET
1,2
FORMULA
Absolute value of Sum_{k=1..n} k^k*(-1)^(k+1). a(n) = n^n - (n-1)^(n-1) + (n-2)^(n-2) - ... - (-1)^n*1^1. - Alexander Adamchuk, Jun 30 2006
MATHEMATICA
Abs[Table[Sum[k^k*(-1)^(k+1), {k, 1, n}], {n, 1, 30}]] (* Alexander Adamchuk, Jun 30 2006 *)
RecurrenceTable[{a[1]==1, a[n]==n^n-a[n-1]}, a, {n, 20}] (* Harvey P. Dale, Jan 21 2015 *)
PROG
(Python)
from itertools import accumulate, count, islice
def A001099_gen(): # generator of terms
yield from accumulate((k**k for k in count(1)), func=lambda x, y:y-x)
A001099_list = list(islice(A001099_gen(), 20)) # Chai Wah Wu, Jun 17 2022
CROSSREFS
Cf. A001923.
Sequence in context: A225107 A249926 A279651 * A277462 A371522 A230325
KEYWORD
nonn
AUTHOR
STATUS
approved